L House : Ketika Tradisi Bertemu Modernitas dalam Satu Bangunan - Alfiatus Sholeha (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
L House is a house design that is shaped like the letter "L". This distinctive configuration offers flexibility in spatial arrangement and creates an interesting interaction between interior and exterior areas. L House by 022Studio is a work that combines modern aesthetics with traditional values and sustainability. Through a descriptive criticism method involving interviews with architects, literature studies, and analysis of design elements, this study aims to reveal the strengths and challenges in the application of modern design in a tropical context. L House successfully integrates space with nature through the use of local materials, flexible spatial layouts, and building orientations that optimize natural lighting and ventilation. In addition, this design also makes a significant contribution to the development of modern architecture in Indonesia by demonstrating that modern buildings can be adapted to local cultural and environmental contexts. L House is a good example of sustainable architecture that can inspire similar projects in the future.